2014
DOI: 10.1111/psj.12042
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Schools: School Choice, Political Learning, and Policy Feedback

Abstract: This article investigates the policy feedback and political learning effects of school vouchers. Of particular interest is how market‐based policies affect the likelihood that program participants will connect their experiences with the policy to the government. I examine parent survey data from an evaluation of the Milwaukee school voucher program. I find that voucher parents are more likely than public school parents to perceive that the government has influenced their child's schooling and to believe that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Half of the studies examining tolerance found that private school choice improved tolerance levels (e.g., Campbell, ; Wolf, Peterson, and West, ), while the remaining half found no significant difference (e.g., Fleming, Mitchell, and McNally, ). Three of five studies found that private school choice boosted civic engagement through increased political participation, volunteering, and charitable activity (Bettinger and Slonim, ; Fleming, ; Fleming, Mitchell, and McNally, ). Furthermore, the only reviewed study on social order found that school choice led to less criminal activity (DeAngelis and Wolf, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Half of the studies examining tolerance found that private school choice improved tolerance levels (e.g., Campbell, ; Wolf, Peterson, and West, ), while the remaining half found no significant difference (e.g., Fleming, Mitchell, and McNally, ). Three of five studies found that private school choice boosted civic engagement through increased political participation, volunteering, and charitable activity (Bettinger and Slonim, ; Fleming, ; Fleming, Mitchell, and McNally, ). Furthermore, the only reviewed study on social order found that school choice led to less criminal activity (DeAngelis and Wolf, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are two reviews of the empirical evidence on how school choice impacts democratic outcomes such as citizenship skills, civic engagement, tolerance of others, and criminal activity. The most recent review (DeAngelis 2017) of the eleven quasi-experimental and experimental studies on the effects of private school choice on civic outcomes finds that effects are null to positive for tolerance (Campbell 2002;Fleming, Mitchell, and McNally 2014;Howell and Peterson 2006;Mills et al 2016;Peterson and Campbell 2001;Wolf, Peterson, and West 2001), null to positive for civic engagement (Bettinger and Slonim 2006;Carlson, Chingos, and Campbell 2017;Fleming 2014;Fleming, Mitchell, and McNally 2014), and positive for crime reduction (DeAngelis and Wolf 2016; DeAngelis and Wolf 2019). Wolf's (2007) meta-analysis and review of twenty-one quantitative studies on the subject, in which he used a less stringent methodology screen than DeAngelis (2017), also finds that school choice largely improves civic outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, some argue that school choice could increase social capital and enhance civic engagement by forcing parents to become better informed about public services (Schneider et al, 1997; but see Cox and Witko, 2008). For example, there is some survey evidence indicating that parents who participate in school voucher programs become more informed and politically active as a result (Fleming 2014), and Lovenheim and Walsh (2018) find that school choice greatly increases the extent to which parents seek school quality information online. 3…”
Section: Introductionmentioning
confidence: 99%